2020
DOI: 10.5430/rwe.v11n5p235
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Among Corporate Governance, Innovation, and Performance in Vietnam’s Banking Sector

Abstract: Background/Objectives: The current research tries to investigate effects of the three elements of corporate governance (chief executive officer duality, board independence and size) on banking performance and then analyze the mediating role of innovation on these effects, which are overlooked at Vietnamese banks.Methods/Statistical analysis: The research sample for this research encompassed 78 usable firm-year observations of 25 publicly listed organizations in the banking sector on Vietnam’s three main Stock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…These findings support the agency theory which recommends that a larger managerial ownership stake will induce managers to make better decisions that lead to better firm performance. This significant and positive relationship align with the findings of Annisa et al (2021), Huynh et al (2020), Faisal (2015, Bhagat and Bolton (2013), Onakoya et al (2013), Tomar and Bino (2012), Fooladi and Ghodratollah (2011), Cornett et al (2009), Krivogorsky (2006), Gedajlovic and Shapiro (2002), Demsetz and Villalonga (2001), R. K. Morck et al (2000), Hart (1995), Mehran (1995), Jensen (1993) who reported positive and significant influence of board ownership on financial performance. Also in tandem with the findings of Alshouha et al (2021), Tayachi et al (2021), Alabdullah (2018), Shleifer and Vishny (1997), Vu et al (2018), Nyaguthii et al (2019), Bhagat and Bolton (2013), Z.…”
Section: Discussion Of Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…These findings support the agency theory which recommends that a larger managerial ownership stake will induce managers to make better decisions that lead to better firm performance. This significant and positive relationship align with the findings of Annisa et al (2021), Huynh et al (2020), Faisal (2015, Bhagat and Bolton (2013), Onakoya et al (2013), Tomar and Bino (2012), Fooladi and Ghodratollah (2011), Cornett et al (2009), Krivogorsky (2006), Gedajlovic and Shapiro (2002), Demsetz and Villalonga (2001), R. K. Morck et al (2000), Hart (1995), Mehran (1995), Jensen (1993) who reported positive and significant influence of board ownership on financial performance. Also in tandem with the findings of Alshouha et al (2021), Tayachi et al (2021), Alabdullah (2018), Shleifer and Vishny (1997), Vu et al (2018), Nyaguthii et al (2019), Bhagat and Bolton (2013), Z.…”
Section: Discussion Of Resultssupporting
confidence: 83%
“…As separation of firm ownership from management (Abu-Serdaneh & Ghazalat, 2022) continues, conflicts of interests between managers and owners will arise in situations where, the management is self-interest seeking, self-serving, individualistic and opportunistic. To mitigate the divergence of interests and consequential agency problems, agency theory suggests that managers and owners interests converge if shareholders institute ownership structure that can monitor and induce managers to make better decisions that lead to better firm performance (Hart, 1995; Huynh et al, 2020). Thus, a larger managerial ownership stake was recommended by the agency theory in order to reduce the need for and costs of monitoring and control.…”
Section: Review Of Related Literaturementioning
confidence: 99%